THE INFLUENCE OF STUDENT LEARNING STYLE ON HIGHER ORDER THINKING SKILL (HOTS) OF CELL STRUCTURE AND FUNCTION TOPIC - Ahmad Ali Pantas; H Hasruddin; Mariaty Sipayung (Jurnal Pelita Pendidikan, 2020)
This research aims to determine the relationship and contribution of visual, auditory and kinesthetic learning styles toward Higher Order Thinking Skills (HOTS) of cell structure and function topic in grade XI Science SMAN 1 Lubuk Pakam with academic year 2017/2018. The population for this research were all students in grade XI Science SMAN 1 Lubuk Pakam was 246 students with sample of research as many as 152 students. This research is an ex-post facto. The data was collected by using questionnaires with Likert scale for learning styles and multiple choices questions for HOTS of cell structure and function topic. Then, the data was analyzed by using linear regression. The results of this research showed that: (1) There was a positive influence and significant of visual learning style towards Higher Order Thinking Skills (HOTS) of students as evidenced by Fcount=11.016 with its contribution was 6.8%; (2) There was a positive influence and significant of auditory learning style towards Higher Order Thinking Skills (HOTS) of students as evidenced by Fcount=6.570 with its contribution was 4.2%; (3) There was a positive influence and significant of kinesthetic learning style towards Higher Order Thinking Skills (HOTS) as evidenced by Fcount=4.464 with its contribution was 2.9% and (4) There was positive influence and significant of visual, auditory and kinesthetic learning style as together towards Higher Order Thinking Skills (HOTS) of students as evidenced by Fcount=8.061 with its contribution was 14%. Keywords: Higher Order Thinking Skill (HOTS),Learning Style